2022
DOI: 10.1111/cdev.13734
|View full text |Cite
|
Sign up to set email alerts
|

Social gaze in preterm infants may act as an early indicator of atypical lateralization

Abstract: Visual field biases have been identified as markers of atypical lateralization in children with developmental conditions, but this is the first investigation to consider early lateralized gaze behaviors for social stimuli in preterm infants. Eye‐tracking methods with 51 preterm (33 male, 92.1% White) and 61 term‐born (31 male, 90.1% White) infants aged 8–10 months from Edinburgh, UK, captured the development of visual field biases, comparing gaze behavior to social and non‐social stimuli on the left versus rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…In addition, at 12 months, more VLBW toddlers than TD toddlers showed leftward attention bias regardless of whether the face was talking, silent, or mouth moving. This may be interpreted as reflecting delayed development of left visual field biases in social cognition in VLBW 21 . Further, it was consistent with the finding that infants showed the left attention bias in MM condition 15 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, at 12 months, more VLBW toddlers than TD toddlers showed leftward attention bias regardless of whether the face was talking, silent, or mouth moving. This may be interpreted as reflecting delayed development of left visual field biases in social cognition in VLBW 21 . Further, it was consistent with the finding that infants showed the left attention bias in MM condition 15 …”
Section: Discussionsupporting
confidence: 87%
“…This may | 1721 be interpreted as reflecting delayed development of left visual field biases in social cognition in VLBW. 21 Further, it was consistent with the finding that infants showed the left attention bias in MM condition. 15…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the present study provided some preliminary indication of lateralisation of face processing at high eccentricities, beyond centrally presented faces and side biases within the face. Although side had a marginal role compared to eccentricity in explaining the detection rates, this bias may emerge from or soon after 9 months of age [28,62]. Future investigations may address whether this effect is more pronounced in older infants and whether there may be a neural correlate of a left visual field superiority for detection of face patterns at the edge of the developing visual field.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, through an alteration in the hypothalamic-pituitary-adrenal axis, early life or chronic stress may lead to atypical cerebral lateralization and to neurodevelopmental or psychiatric disorders (Berretz et al, 2020). Following this view, Davis et al (2022) showed that prematurity, which is related to early life stress (Field & Diego, 2008), exhibits atypical functional lateralization.…”
Section: Discussionmentioning
confidence: 99%
“…Following this view, Davis et al. (2022) showed that prematurity, which is related to early life stress (Field & Diego, 2008), exhibits atypical functional lateralization. As a non‐planned complementary analysis (see Appendix 5), we tested the relation between prematurity, handedness, and neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%